The Effect of Digital Leadership Style, Compensation, and Employee Engagement on Employee Loyalty Through the Performance of Generation Z Employees at Sinar Mas Insurance - Lingga, Herlita Sanawati; Karambut, Fermico; Simatupang, Batara Maju; Putri, Vidiyanna Rizal (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to examine and analyze the direct influence of digital leadership style, compensation, and employee engagement on employee performance, as well as their influence on employee loyalty through performance as a mediating variable among Generation Z employees at PT Asuransi Sinar Mas. The research variables consist of Digital Leadership Style, Compensation, and Employee Engagement as independent variables, Employee Loyalty as the dependent variable, and Employee Performance as the mediating variable. The research method used is a quantitative descriptive approach with an explanatory design. Primary data were collected through questionnaires from 200 Generation Z employee respondents selected using a convenience sampling technique. The research stages include validity testing, reliability testing, classical assumption testing (multicollinearity, heteroscedasticity, and normality), and data analysis using path analysis with the SPSS program. The results of the study indicate that digital leadership style, compensation, and employee engagement simultaneously and partially have a positive and significant effect on employee performance. In addition, employee performance is empirically proven to play a significant role in linking the three independent variables to employee loyalty. Employee engagement was found to be the most dominant driver of loyalty. As managerial advice, companies should continue strengthening their digital leadership ecosystem and investing in psychological well-being programs to enhance employee retention. Furthermore, management is advised to implement an open recruitment system to remain competitive and transparent, mitigate the risk of young talent turnover, and optimize productivity to foster long-term loyalty.